The law of healthcare administration - Showalter, J. Stuart (AUPHA/HAP Book., 2015)
This book examines healthcare law in the United States from the management perspective. The author addresses the significant changes the 2010 Affordable Care Act (ACA) makes to the healthcare industry, including provisions relating to taxation and compliance, the development of accountable care organizations, and new privacy rules under HIPAA. This updated edition includes: an extensive discussion of the major changes occasioned by the ACA; the antitrust decision Federal Trade Commission v. Phoebe Putney Health System; quality issues related to accountable care organizations and The Joint Commission's accreditation standards; the ACA's Shared Savings Program and its effect on further hospital-physician alignment and physician employment; and the Foreign Corrupt Practices Act. --